Evaluation of APTES-Functionalized Zinc Oxide Nanoparticles for Adsorption of CH4 and CO2 - Luis A. Montejo-Mesa; Alicia M. Díaz-García; Celio L. Cavalcante; Enrique Vilarrasa-García; Enrique Rodríguez-Castellón; Daniel Ballesteros-Plata; Giselle I. Autié-Castro (Molecules)
ZnO nanoparticles functionalized with APTES were obtained to evaluate their CH4 and CO2 adsorption at 298 K in a range between 0 and 10 bar. First, ZnO nanoparticles were obtained by a precipitation method and subsequently coated with (3-aminopropyl)triethoxysilane (APTES). As a preliminary study, the results were compared with previously reported naked nanoparticles in order to evaluate the influence of APTES coating on CO2 selectivity. UV-Vis, FT-IR spectroscopy, TGA, XRD, TEM/EDX, XPS and N2 adsorption at 77 K were used to characterize the evaluated material. It was observed that the amount of gas adsorbed on the surface of the nanostructure was very small in comparison with other materials traditionally used for this purpose but slightly higher than those obtained in naked nanoparticles evaluated in previous studies. The affinity of CO2 for the amines groups of the APTES ligand was also discussed.